Inclusive charm production in two-photon collisions at LEP - Dova, María Teresa (1999)
The cross section of charm production in γγ collisions <mtext>σ(e</mtext>+<mtext>e</mtext>−<mtext>→e</mtext>+<mtext>e</mtext>−<mtext>c</mtext><mtext>c</mtext><mtext>̄</mtext><mtext>X)</mtext> is measured at LEP with the L3 detector at centre-of-mass energies from 91 GeV to 183 GeV. Charmed hadrons are identified by electrons and muons from semileptonic decays. The direct process <mtext>γγ→c</mtext><mtext>c</mtext><mtext>̄</mtext> is found to be insufficient to describe the data. The measured cross section values and event distributions require contributions from resolved processes, which are sensitive to the gluon density in the photon.